The effects of leaf harvesting on the morphology, reproduction and sap production of the Cape Aloe (Aloe Ferox) - Greengrass, Catherine (Department of Biological Sciences, 2017)
Harvesting of Aloeferox was estimated (in 1996) to bring in an annual income ofR4 million per year to rural communities alone - a vital source of income for full-time tappers who rely solely on Aloe ferox as their only form of financial survival. They are joined on occasion by casual-tappers who rely on tapping to supplement their incomes in times of hardship (Newton and Vaughan 1996). Landowner's also benefit by allowing harvesting on their land in exchange for a percentage of the harvest (Newton and Vaughan 1996). Trade in bitters sap or gel far outweighs that of other plant parts so care is taken by harvesters to keep the plants alive for future tapping. Leaves from only the lower third of the leaf rosette ( 10 - 15 leaves) are harvested, and 2 - 4 cm at the base of the leaves are left to prevent damage to vascular tissues (Newton and Vaughan 1996, Mac Farlane 2004). Populations are only harvested every 18 - 36 months allowing plants to recover from the loss of leaf material. Plants suffering from insect-infestation or disease are not harvested to avoid weakening the plant further and possibly causing death (Newton and Vaughan 1996). Effort is also made by landowners to relocate plants growing in areas they plan to transform and to monitor harvesting activities on their properties (Newton and Vaughan 1996). The vested interest in keeping the plants alive has inadvertently assured the preservation of populations at past harvesting levels although no formal conservation or resource management policy presently exists for A. ferox (Newton and Vaughan 1996). Effects of harvesting, which are not limited to the direct effect of leaf removal on the plant but include indirect effects - such as reduced reproductive output, reduced sap production and even trampling of recruits - have nonetheless raised concern for the long-term survival of populations (Newton and Vaughan 1996). This study addressed some of the indirect effects of harvesting on Aloe ferox on both population and individual plants levels. On the population level plant density, mortality, susceptibility to disease and sizeclass structure was compared between unharvested and harvested populations. On the individual plant level vegetative traits, flower production and sap production were compared between unharvested and harvested plants. One of few other studies on ecology of A. ferox by Hoffman (1988) assessed some of these characteristics for a population in Port Elizabeth, South Africa.